Germ–Somatic Cell Interactions Are Involved in Establishing the Follicle Reserve in Mammals - Rodrigues, Patrícia; Limback, Darlene; McGinnis, Lynda; Marques, Mónica; Aibar, Juan; Plancha, Carlos E. (Frontiers in Cell and Developmental Biology, 2021)
Mammalian females are born with a finite reserve of ovarian follicles, the functional units of the ovary. Building an ovarian follicle involves a complex interaction between multiple cell types, of which the oocyte germ cell and the somatic granulosa cells play a major role. Germ-Somatic cell interactions are modulated by factors of different cell origins that influence ovarian development. In early development, failure in correct Germ-Somatic cell communication can cause abnormalities in ovarian development. These abnormalities can lead to deficient oocyte differentiation, to a diminished ovarian follicle reserve and consequently to early loss of fertility. However, Oocyte-Granulosa cell communication is also extremely important for the acquisition of oocyte competence until ovulation. In this paper we will visit the establishment of follicle reserve, with particular emphasis in Germ-Somatic cell interactions, and their importance for human fertility.